2020
DOI: 10.1111/1744-7917.12823
|View full text |Cite
|
Sign up to set email alerts
|

A new bacteria‐free strategy induced by MaGal2 facilitates pinewood nematode escape immune response from its vector beetle

Abstract: Symbiotic microbes play a crucial role in regulating parasite-host interactions; however, the role of bacterial associates in parasite-host interactions requires elucidation. In this study, we showed that, instead of introducing numerous symbiotic bacteria, dispersal of 4th-stage juvenile (J IV ) pinewood nematodes (PWNs), Bursaphelenchus xylophilus, only introduced few bacteria to its vector beetle, Monochamus alternatus (Ma). J IV showed weak binding ability to five dominant bacteria species isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Differences in microbiota between the two dispersal stages may also rise from their exposure to the surrounding microbiota environment: first, by molting to fourth-stage dispersal juveniles, the larvae likely decrease their microbiota load before entering the vector, and second, because these fourth-stage dispersal juveniles lack functioning mouths, they are less likely to acquire microbiota. Besides these factors, differences in type and number of cuticle proteins between the two dispersal stages of pinewood nematode may also contribute to the observed differences in microbiota composition by affecting their abilities to carry bacteria ( 22 , 39 ). Similarly, low diversity of microbiota has also been found in dauer juveniles of other nematode species ( 40 ), and some studies have shown that entomophilic nematodes do not carry their own bacterial communities during host infestations ( 38 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in microbiota between the two dispersal stages may also rise from their exposure to the surrounding microbiota environment: first, by molting to fourth-stage dispersal juveniles, the larvae likely decrease their microbiota load before entering the vector, and second, because these fourth-stage dispersal juveniles lack functioning mouths, they are less likely to acquire microbiota. Besides these factors, differences in type and number of cuticle proteins between the two dispersal stages of pinewood nematode may also contribute to the observed differences in microbiota composition by affecting their abilities to carry bacteria ( 22 , 39 ). Similarly, low diversity of microbiota has also been found in dauer juveniles of other nematode species ( 40 ), and some studies have shown that entomophilic nematodes do not carry their own bacterial communities during host infestations ( 38 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced microbiota load in the fourth-stage dispersal juveniles may therefore be an adaptation to improve their loading success to the insect vector by reducing the risk of accidental introduction of harmful bacteria that could, for instance, lower the beetle’s fitness or increase the likelihood of triggering the beetle’s immune response. Interestingly, pinewood nematodes can even benefit the vector by reducing bacteria, particularly opportunistically pathogenic taxa, in the beetle’s tracheae ( 39 ). However, because in this study we focused on the pinewood nematode stages that are most relevant for the transmission of the pine wilt disease (the two dispersal stages), the question of whether the succession and assembly processes of microbial community differ among propagative and dispersal stages of pinewood nematodes, and whether the low microbiota diversity in the fourth-stage dispersal juveniles is an adaptation to vector-mediated transmission, should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many biological characteristics of insect-vectored nematodes have been degraded due to the establishment of a mutualistic relationship between nematodes and their vectors. For example, in order to reduce the likelihood of triggering its vector's immune response, pinewood nematode B. xylophilus molts before entering into the vector trachea to remove most of the symbiotic microbes adhering to its body surface (Zhang et al, 2021 ). In addition, the nematode's oral orifice is degenerated and forms a closed body cavity, which may prevent the bacteria and/or secretions from flowing out from its intestine into the insect vector (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in order to reduce the likelihood of triggering its vector's immune response, pinewood nematode B. xylophilus molts before entering into the vector trachea to remove most of the symbiotic microbes adhering to its body surface (Zhang et al, 2021 ). In addition, the nematode's oral orifice is degenerated and forms a closed body cavity, which may prevent the bacteria and/or secretions from flowing out from its intestine into the insect vector (Zhang et al, 2021 ). These results suggest that both nematodes and their vectors reduce immune recognition and defense against each other to balance their mutualistic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The vector beetles ( M. alternatus and M. saltuarius ) were surface-sterilized by using ethanol and then rinsed three times with sterile water. Tracheae of vector beetles were extracted under the CKX53 microscope (Olympus, Tokyo, Japan) (Zhou et al, 2018 ; Zhang et al, 2020a ). In total, we collected 394 vector beetles.…”
Section: Methodsmentioning
confidence: 99%